Integrated planning model of creative industry based Kampung tourism in Jayengan Surakarta, Indonesia - Astuti, W. (Malaysian Institute Of Planners, 2017)
Creative Industry-based tourism has been popular as several cities in Indonesia have also been declared as "Creative City". In sustainability viewpoint, the integration of creative industry activities with other planning elements and efforts towards social and economic development is necessary. The inter-organizational collaboration is essential by integrating various disciplines in managing the complexity and the dynamics in tourism development. This research aims at developing an Integrated Planning Model of Creative Industry-based Tourism in Jayengan Surakarta. The study adopted a mixed-methods approach using detailed observations and interviews, as well as Focus Group Discussion (FGD) with the primary actors to understand the process. The study suggests that creative industry-based kampung tourism in Jayengan Surakarta, must be developed with integrated manner through interrelationships among tourism components, developing problem-solving model, promoting a conceptual system to guide the process and strengthening the inter-organizational collaboration. It is also understood that this concept might promote rural development since the potential sources of local industries and tourism are abundantly available in the rural areas.